Knowledge of and attitudes towards concussion in cycling: A preliminary study - Hurst, H. T.; Novak, A. R.; Cheung, S. S.; Atkins, S. (Journal of Science and Cycling, 2019)
The aim of this study wasto investigate the knowledge of and attitudes towards concussion in cycling. An abbreviated Rosenbaum Concussion Knowledge and attitudes Survey (RoCKAS) was distributed online via social media and completed by 1990 respondents involved in cycling. The RoCKAS comprised separate sections to determine a concussion knowledge index (CKI) providing a score between 0-33, and a concussion attitudes index (CAI) with possible scores between 7-20. Mean scores were 25.9 ± 11.0 and 17.7 ± 3.0 for CKI and CAI, respectively. However, there remained several concussion knowledge misconceptions and disparity between reported knowledge and attitudes and actions, with 16% of respondents admitting to riding despite having concussive symptoms and 18.7% stating they would hide a concussion to stay in an event. The results of this survey indicate those involved with cycling reported reasonable knowledge of concussion symptoms and safe/desirable attitudes towards concussion education. However, despite reporting safe attitudes, the actions of those involved in cycling may be of greater concern, as a considerable number of respondents were still willing to take risks by continuing to cycle knowing they had concussive symptoms.